PENGARUH PELAYANAN DAN FASILITAS KESEHATAN DARURAT COVID (FKDC) TERHADAP KEPUASAN PASIEN COVID-19 DI ASRAMA HAJI SLEMAN D.I. YOGYAKARTA: Pelayanan, Fasilitas Kesehatan dan Kepuasan - fahlefi, wilis; Yuliantoharinugroho; Mochamad Rofik; Eva Lutfiana (LPPM Akademi Manajemen Administrasi Yogyakarta, 2025)
The purpose of this research is to determine the effect of Covid emergency health services and facilities (FKDC) on COVID-19 patient satisfaction at the Sleman Hajj Dormitory in Yogyakarta Special Region. The population in this research is all Covid patients in the Sleman Hajj dormitory, D.I Yogyakarta in February 2022, totaling 107 people, while the sample used a random sample of 84 people. Data collection is carried out by distributing questionnaires to respondents. Collection techniques using SPSS.17. Analyze data using multiple regression. Based on the research results, it is stated that services and facilities have a significant and influential effect on the satisfaction of Covid patients at the Sleman D.I. Hajj dormitory. Yogyakarta. Keywords: Service, Facilities and Satisfaction